RETRACTED: Simulation model of energy exchange in an intelligent decision-making system based on a multi-agent neurocognitive architecture - Pshenokova Inna; Bzhikhatlov Kantemir; Nagoeva Olga (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001